Development of pristine and Au-decorated Bi2O3/Bi2WO6 nanocomposites for supercapacitor electrodes - Gote, Gorkshnath H.; Pathak, Mansi; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2019)
Pristine and Au-decorated Bi2O3/Bi2WO6 nanocomposites were synthesized via a facile hydrothermal method. Characterization techniques such as XRD, FESEM, HRTEM and XPS were used to explore the structural, morphological and electronic properties. Furthermore, electrochemical characterizations including cyclic voltammetry (CV), the galvanostatic charge-discharge (GCD) method, and electrochemical impedance spectroscopy (EIS) were performed to investigate the supercapacitance behaviour of the synthesized materials. Interestingly, the Au-decorated Bi2O3/Bi2WO6 nanocomposite showed a higher capacitance of 495.05 F g(-1) (1 M aqueous KOH electrolyte) with improved cycling stability (99.26%) over 2000 cycles, measured at a current density of 1 A g(-1), when compared to the pristine Bi2O3/Bi2WO6 composite (capacitance of 148.81 F g(-1) and good cycling stability (95.99%) over 2000 cycles at a current density of 1 A g(-1)). The results clearly reveal that the decoration of the Bi2O3/Bi2WO6 composite with Au nanoparticles enhances its supercapacitance behaviour, which can be attributed to an increase in electrical conductivity, good electrical contact between the electrode and electrolyte, and an increase in effective area. The Au-decorated Bi2O3/Bi2WO6 nanocomposite can be considered as an electrode material for supercapacitor application.

Realization of efficient field emitter based on reduced graphene oxide-Bi2S3 heterostructures - Gote, Gorkshnath H.; Bhopale, Somnath R.; More, Mahendra A.; Late, Dattatray J. (Physica Status Solidi A-Applications and Materials Science, 2019)
Herein, Bi2S3 nanorods and reduced graphene oxide (rGO)-Bi2S3 heterostructures are synthesized using a simple hydrothermal method. The structural, morphological, chemical, and elemental analysis of as-synthesized materials is performed using X-ray diffraction (XRD), Raman spectroscopy, field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Field emission (FE) studies are carried out on both pristine Bi2S3 nanorods and rGO-Bi2S3 heterostructure samples at a base pressure of approximate to 1 x 10(-8) mbar. The results show that the rGO-Bi2S3 heterostructure emitter has superior FE performance compared to pristine Bi2S3 emitters in terms of the turn-on field (2.6 V mu m(-1) at 10 mu A cm(-2)) and threshold field (4.0 V mu m(-1) at 100 mu A cm(-2)) along with a high emission current density of approximate to 1464 mu A cm(-2) at an applied electric field of 7.0 V mu m(-1). The rGO-Bi2S3 heterostructure emitter exhibits very good emission current stability, tested for more than 3 h duration, characterized by standard deviation values approximate to 2.84 and 4.06, corresponding to preset values 12 and 100 mu A. This study implies that one-step hydrothermal route can be efficiently used to synthesize organic-inorganic heterostructures that possess unique morphology. Furthermore, the synthesized rGO-Bi2S3 heterostructure emitter shows potential as an electron source for practical application in vacuum microelectronic devices.
Keywords: Bi2S3; field emission; Heterostructures; Nanorods; Reduced graphene oxide